Metriorhynchid crocodylomorphs from the lower Kimmeridgian of Southern Germany: evidence for a new large-bodied geosaurin lineage in Europe. Issue 2 (2nd April 2020) - Abel, Pascal; Sachs, Sven; Young, Mark Thomas
Abstract: Over the last two centuries, numerous exquisitely preserved thalattosuchian crocodylomorph skeletons have been found in the Jurassic strata of Southern Germany. While the majority of these specimens occur in Toarcian and upper Kimmeridgian–lower Tithonian deposits, thalattosuchian remains are otherwise rare in strata representing different stages of the Jurassic. Here, we describe skeletal elements from two large-bodied thalattosuchians attributable to the family Metriorhynchidae – these were recovered from lower Kimmeridgian sediments in Bavaria and Baden-Württemberg, respectively. These new metriorhynchid fossils are closely comparable in both stratigraphic age and dental morphology, and thus may be congeneric. Furthermore, our phylogenetic analysis suggests affinity with metriorhynchid remains from France, Switzerland, and the UK. We interpret these taxa as members of an as-yet unnamed geosaurine metriorhynchid lineage (herein termed the 'E-clade') from the Kimmeridgian and Tithonian of Europe, which appears to be related to species of Torvoneustes from England and Mexico, and Purranisaurus potens from Argentina, collectively contributing to 'Subclade T' of the tribe Geosaurini. Finally, the metriorhynchid material described herein suggests preservation as a 'bloat and float' carcass that underwent diagenetic dispersal within a limestone-marl-alternation deposited in an off-shore epicontinental marine environment. Pascal Abel [pascal.abel@senckenberg.de ], Senckenberg Center for Human Evolution and Palaeoenvironment, Eberhard-Karls-University Tübingen, Sigwartstraße 10, 72076 Tübingen, Germany; Sven Sachs [sachs.pal@gmail.com ], Naturkunde-Museum Bielefeld, Abteilung Geowissenschaften, Adenauerplatz 2, 33602 Bielefeld, Germany; Mark T. Young [marktyoung1984@gmail.com ], School of GeoSciences, Grant Institute, University of Edinburgh, James Hutton Road, Edinburgh, EH9 3FE, UK.